2016
DOI: 10.3748/wjg.v22.i38.8459
|View full text |Cite
|
Sign up to set email alerts
|

Towards a new paradigm of microscopic colitis: Incomplete and variant forms

Abstract: Microscopic colitis (MC) is a chronic inflammatory bowel disease that has emerged in the last three decades as a leading cause of chronic watery diarrhoea. MC classically includes two main subtypes: lymphocytic colitis (LC) and collagenous colitis (CC). Other types of histopathological changes in the colonic mucosa have been described in patients with chronic diarrhoea, without fulfilling the conventional histopathological criteria for MC diagnosis. Whereas those unclassified alterations remained orphan for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 81 publications
0
14
0
3
Order By: Relevance
“…Nonetheless, other research showed that no change in the mean thickness of the collagen band had been reported, even after trea tment with Budesonide [1,5,6]. On the other hand, it seems likely that the change of one subtype of MC to another one is quite possible [4]. Researchers from the Karolinska Institutet Marie-Rose Mellander [10] reported such observations during an MC cohort: "Histological change of phenotype over time was not uncommon and was observed in 12% of the patients (10 CC to LC, 13 LC to CC)".…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Nonetheless, other research showed that no change in the mean thickness of the collagen band had been reported, even after trea tment with Budesonide [1,5,6]. On the other hand, it seems likely that the change of one subtype of MC to another one is quite possible [4]. Researchers from the Karolinska Institutet Marie-Rose Mellander [10] reported such observations during an MC cohort: "Histological change of phenotype over time was not uncommon and was observed in 12% of the patients (10 CC to LC, 13 LC to CC)".…”
Section: Discussionmentioning
confidence: 98%
“…The apparent incidence and prevalence of MC is much higher than initially thought. Increases in the reported incidence are observed [4]. Is this a genuine rise in incidence rates or rather the consequence of better detection of the disease?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The diagnosis of collagenous colitis is characterised by irregular thickened collagen band (>10 μm) beneath the surface epitelium 15. The advent of high-definition colonoscopes has led to discovery of distinctive endoscopic findings such as pseudomembranes, pruning of the mucosal vascular pattern and mucosal breaks in association with collagenous colitis 16 17…”
Section: Discussionmentioning
confidence: 99%